Penerapan Pembelajaran Berbasis Predict, Observe, Explain (Poe) pada Pembelajaran Geometri di Kelas X SMA Negeri 13 Palembang - Yanuarti, Sri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
This purpose of study is to know the application of learning Predict, Observe, Explain (POE) and achievement of the ten grade students of SMA Negeri 13 palembang in learning geometry. The subject in grade X MIPA 6 class with 40 students academic year 2015/2016. To collect the data observation and tests were used. The result of study showed that the application of learning POE was very successful in terms of teacher’s activities the activities of the students was conducted with final score 63,54 which categorized average. The result of the students’ achievement was good when Predict, Observe, Explain (POE) study was conducted in topic distance of 3 dimension. From the test, the students who have high score was 2,6%, the students who have good score was 7,7%, the students who have average score was 46,15% and the students who have low score was 43,6 %.